2018
DOI: 10.1001/jama.2017.21640
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Calcium, or Combined Supplementation for the Primary Prevention of Fractures in Community-Dwelling Adults

Abstract: Vitamin D supplementation alone or with calcium was not associated with reduced fracture incidence among community-dwelling adults without known vitamin D deficiency, osteoporosis, or prior fracture. Vitamin D with calcium was associated with an increase in the incidence of kidney stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 38 publications
4
146
1
8
Order By: Relevance
“…This large study dominated the Cochrane meta‐analyses. In a more recent meta‐analyses by Kahwati and colleagues no increased incidence of stones was found. However, the recent evidence report compiled for the US Preventive Services Task Force (USPSTF) (which included the WHI and two studies by Lappe and colleagues) also found an increased risk for kidney stones in combined supplementation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This large study dominated the Cochrane meta‐analyses. In a more recent meta‐analyses by Kahwati and colleagues no increased incidence of stones was found. However, the recent evidence report compiled for the US Preventive Services Task Force (USPSTF) (which included the WHI and two studies by Lappe and colleagues) also found an increased risk for kidney stones in combined supplementation.…”
Section: Discussionmentioning
confidence: 88%
“…The increased risk occurs at lower concentrations of 25(OH)D in black Americans than in white Americans . Finally, a recent systematic analysis carried out for the US Public Health Task Force resulted in a recommendation against using vitamin D supplements for prevention of falls and fractures in community dwelling adults who do not have osteoporosis or vitamin D deficiency . This recommendation in part emanated from omitting studies that included subjects with vitamin D deficiency from consideration.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The USPSTF analysed 11 randomized clinical trials (N = 51 419) in adults 50 years and older conducted over 2 to 7 years. 12,13 The USPSTF found adequate evidence that daily supplementation with 400 IU or less of vitamin D and 1000 mg or less of calcium has no benefit for the primary prevention of fractures in community-dwelling, post-menopausal women. 12,13 In…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, laboratory and epidemiological studies have also suggested that low vitamin D status may be associated with a variety of health risks, including respiratory illnesses (infections and asthma), adverse pregnancy outcomes, and chronic diseases of adulthood, such as osteoporosis and cardiovascular disease . To date, clinical trials have contributed a limited amount of empirical evidence to support the beneficial effects of vitamin D, primarily on the risk of respiratory infections and some adverse pregnancy outcomes; however, there is limited evidence thus far from randomized clinical trials to support effects on health outcomes other than bone health …”
Section: Vitamin D Physiologymentioning
confidence: 99%